The Uro Dyna-CT enables three-dimensional planned laser-guided complex punctures - Ritter, Manuel; Rassweiler-Seyfried, Marie-Claire; Michel, Maurice Stephan (European urology, 2015)
Ultrasound and fluoroscopy are the standard imaging techniques used to perform punctures in urology. Cross-sectional and three-dimensional (3D) imaging may enable safer procedures, especially in complex cases. To assess the feasibility of 3D planned laser-guided punctures in urology performed with the Uro Dyna-CT (Siemens Healthcare Solutions, Erlangen, Germany). A total of 27 punctures using the laser-guided system syngo iGuide (Artis Zee Ceiling; Siemens Healthcare Solutions, Erlangen, Germany) for the Uro Dyna-CT have been performed to date. Patients with complex puncture indications due to unclear ultrasound findings or a suspicion of surrounding bowel were included. Image acquisition was performed using a customized 8s syngo iGuide protocol of the Uro Dyna-CT. The puncture tract was planned after 3D and cross-sectional image reconstruction. The puncture was performed supported by the laser-guiding system. The primary end point of our assessment was accuracy and applicability of the system in a clinical setting. Secondary end points were planning time, puncture time, and radiation exposure of the patient. Overall, 24 of 27 punctures were successful. No severe complications occurred. Median radiation dose of the Uro Dyna-CT scan was 6113.1 micrograys meter squared (μGym2; range: 1081.6-7957.2μGym2). The small patient cohort is the major limitation of our study. We believe the Uro Dyna-CT-based puncture technique is an excellent additional instrument that allows the urologist to handle complex punctures. Image acquisition leads to higher radiation doses than standard fluoroscopy but does not exceed the radiation exposure of alternative procedures such as computed tomography (CT)-guided punctures with multidetector CT, which is used mainly for complex cases. We report our experience with a three-dimensional planning and laser-guiding tool to perform complex punctures for urologic indications. The technique is feasible in the endourologic intervention suite.